242. Seasonality in antibiotic use and resistance across multiple bacterial pathogens and antibiotic classes. (31st December 2020) - Sun, Daphne S; Kissler, Stephen M; Kanjilal, Sanjat; Olesen, Scott; Grad, Yonatan H
Abstract: Background: Antibiotic use is an important driver of antibiotic resistance. Previous studies have shown that this relationship is detectable on a seasonal timescale, where seasonally cycling antibiotic prescribing corresponds with cycling levels of resistance. Here, we evaluated the seasonal relationship between antibiotic use and resistance across multiple species and antibiotic classes in Boston, Massachusetts. Methods: To conduct our study, we analyzed antibiotic claims data from the Massachusetts All Payers Claims Database for five antibiotic classes, beta-lactams, macrolides, quinolones, tetracyclines, and nitrofurans, which together account for 74% of the total outpatient antibiotic claims in this dataset. In addition, we analyzed antibiotic susceptibility data for clinical isolates collected from two tertiary care hospitals, focusing on three clinically important bacterial pathogens. Our analysis included a total of 131, 815 Escherichia coli, 47, 208 Staphylococcus aureus, and 27, 237 Klebsiella pneumoniae isolates collected over the years 2007–2019, with susceptibility testing data for 5–6 antibiotics per species. To determine the extent of seasonality in use and resistance, we fit the antibiotic claims data for each antibiotic class and the minimum inhibitory concentration (MIC) data for each species-antibiotic combination to a sinusoidal model with either a 6 or 12-month period. Results: We found that use of all 5 antibiotic classes and resistance in 9 out of 15 species-antibiotic combinations showed a significant amplitude of seasonality (p-value < 0.05). Despite different seasonal peaks in antibiotic use across classes, resistance peaked in the winter for almost all species-antibiotic combinations and was most highly correlated with use of winter-peaking antibiotic classes, beta-lactams and macrolides. Conclusion: Overall, these results suggest that co-resistance and "bystander" selection – selection for resistance in asymptomatically colonizing and potentially pathogenic bacteria that are not the direct target of treatment – mediate the effects of antibiotic prescribing on the landscape of resistance. Disclosures: All Authors : No reported disclosures